Development of an Intracranial Dural Arteriovenous Fistula after Venous Sinus Stenting for Idiopathic Intracranial Hypertension. (21st March 2018) - Buell, Thomas J; Raper, Daniel M; Ding, Dale; Chen, Ching-Jen; Liu, Kenneth C
Abstract : We report a case in which an intracranial dural arteriovenous fistula (DAVF) developed after endovascular treatment of a patient with idiopathic intracranial hypertension with venous sinus stenting (VSS). The pathogenesis may involve hemodynamic alterations secondary to increased poststenting venous sinus pressure, which may cause new arterial ingrowth into the fistulous sinus wall without capillary interposition. Despite administration of dual antiplatelet therapy, there may also be subclinical cortical vein thrombosis that contributed to DAVF formation. In addition to the aforementioned mechanisms, increased inflammation induced by VSS may upregulate vascular endothelial growth factor and platelet-derived growth factor expression and also promote DAVF pathogenesis. Since VSS has been used to obliterate DAVFs, DAVF formation after VSS may seem counterintuitive. Previous stents have generally been closed cell, stainless steel designs used to maximize radial compression of the fistulous sinus wall. In contrast, our patient's stent was an open cell, self-expandable nitinol design (Protégé Everflex). Neurointerventionalists should be aware of this potential, although rare complication of DAVF formation after VSS.